THE IMPACT OF POLITICAL LEGAL DEVELOPMENTS ON LAW ENFORCEMENT IN INDONESIA - Ismaidar; Anwar Ibrahim (RADJA PUBLIKA, 2024)
Laws are guidelines and rules related to the concept of social life and will always be in accordance with the conditions of society. Law is a demand to be able to provide justice, meaning that law is always faced with the question of whether the law can achieve justice. Related to this legal concept, legal politics is defined as activities that determine patterns and ways of forming laws, overseeing the operation of laws, and updating laws for the purposes of the State. Therefore, law is a determinant of politics, and is also related to democracy in the sense that political activities are regulated and must comply with legal rules. Law is viewed from the perspective of das sollen (necessity), viewing that law must be guided by the relationships between members of society. Meanwhile, those who view it from the point of view of das sein (reality), empiricists see that law is greatly influenced by politics, not only in the process of making it, but also in its empirical realities. So that law is influenced by politics and even today, legal autonomy in Indonesia is often intervened by politics, not only in terms of its creation, but also in its implementation, both in terms of law enforcement. This research aims to find out what is the impact of legal political developments on law enforcement in Indonesia? How does legal politics exist in law enforcement in Indonesia? The method used in research is normative juridical.